Implementasi Model Pembelajaran Gallery Walk Terhadap Keaktifan Belajar Siswa Pada Mata Pelajaran PPKN - Delvia Oktalia; Siti Tiara Maulia (Shofanah Media Berkah, 2023)
Effective education will encourage intellectual, active and creative development, and change one's personal or professional identity based on the experience or knowledge concerned. In order for students to learn effectively and achieve certain goals, teachers must be persistent in developing lessons using various methods, models and teaching techniques. The formulation of the research problem is how is the implementation of the gallery learning model running on student learning activeness in PPKn?. The purpose of this study was to describe the implementation of the gallery walk learning model for student learning activeness in PPKn. The research method used is descriptive qualitative research. Data collection techniques used are observation, interview, documentation and triangulation techniques. The data analysis technique used is data reduction, data display and data verification. The results showed that the application of the gallery walk learning model to student learning activeness in PPKn was by planning, implementing and evaluating the gallery walk learning model to increase student learning activity and in accordance with planning and implementation..